Cyclodextrin modified PLLA parietal reinforcement implant with prolonged antibacterial activity. (15th April 2017) - Vermet, G.; Degoutin, S.; Chai, F.; Maton, M.; Flores, C.; Neut, C.; Danjou, P.E.; Martel, B.; Blanchemain, N.
Graphical abstract: Abstract: The use of textile meshes in hernia repair is widespread in visceral surgery. Though, mesh infection is a complication that may prolong the patient recovery period and consequently presents an impact on public health economy. Such concern can be avoided thanks to a local and extended antibiotic release on the operative site. In recent developments, poly-l -lactic acid (PLLA) has been used in complement of polyethyleneterephthalate (Dacron®) (PET) or polypropylene (PP) yarns in the manufacture of semi-resorbable parietal implants. The goal of the present study consisted in assigning drug reservoir properties and prolonged antibacterial effect to a 100% PLLA knit through its functionalization with a cyclodextrin polymer (polyCD) and activation with ciprofloxacin. The study focused i) on the control of degree of polyCD functionalization of the PLLA support and on its physical and biological characterization by Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry (DSC) and cell viability, ii) on the understanding of drug/meshes interaction using mathematic model and iii) on the correlation between drug release studies in phosphate buffer saline (PBS) and microbiological evaluation of meshes and release medium against E. coli and S. aureus . All above mentioned tests highlighted the contribution of polyCD on the improved performances of the resulting antibacterial implantable material. Statement of Significance: 1. We managed for the first time, with well-defined parameters in terms of temperature and time of treatment, to functionalize a bio-absorbable synthetic material to improve drug sorption and drug release properties without affecting its mechanical properties. 2. We analyzed for the first time the degradation of our coating products by mass spectroscopy to show that only citrate and cyclodextrin residues (and glucose units) without any cytotoxicity are formed. 3. We managed to improve the mechanical properties of the PLA with the cyclodextrin polymer to form a composite. The assembly (cyclodextrin polymer and PLLA) remains biodegradable.